Medication self-management interventions for persons with stroke: A scoping review. - Lauren Cadel; Stephanie R Cimino; Glyneva Bradley-Ridout; Sander L Hitzig; Tejal Patel; Chester H Ho; Tanya L Packer; Aisha K Lofters; Shoshana Hahn-Goldberg; Lisa M McCarthy; Sara J T Guilcher (PLoS ONE)
The use of multiple medications is common following a stroke for secondary prevention and management of co-occurring chronic conditions. Given the use of multiple medications post-stroke, optimizing medication self-management for this population is important. The objective of this scoping review was to identify and summarize what has been reported in the literature on interventions related to medication self-management for adults (aged 18+) with stroke. Electronic databases (Ovid Medline, Ovid Embase, EBSCO CINAHL, Ovid PsycINFO, Web of Science) and grey literature were searched to identify relevant articles. For inclusion, articles were required to include an adult population with stroke undergoing an intervention aimed at modifying or improving medication management that incorporated a component of self-management. Two independent reviewers screened the articles for inclusion. Data were extracted and summarized using descriptive content analysis. Of the 56 articles that met the inclusion criteria, the focus of most interventions was on improvement of secondary stroke prevention through risk factor management and lifestyle modifications. The majority of studies included medication self-management as a component of a broader intervention. Most interventions used both face-to-face interactions and technology for delivery. Behavioural outcomes, specifically medication adherence, were the most commonly targeted outcomes across the interventions. However, the majority of interventions did not specifically or holistically target medication self-management. There is an opportunity to better support medication self-management post-stroke by ensuring interventions are delivered across sectors or in the community, developing an understanding of the optimal frequency and duration of delivery, and qualitatively exploring experiences with the interventions to ensure ongoing improvement.